Impact of liposome bupivacaine on the adequacy of pain management and patient experiences following aesthetic surgery: Results from an observational study. Issue 1 (March 2015) - Edwards, Michael C; Sorokin, Evan; Brzezienski, Mark; Nahai, Farzad R; Scranton, Richard; Wall, Holly; Wall, Simeon; Finical, Stephan; Smith, Kevin
Background: Despite the efficacy of opioid analgesics for postsurgical pain, they are associated with side effects that may complicate recovery. Liposome bupivacaine is a prolonged-release formulation of bupivacaine approved for intraoperative administration at the surgical site for postsurgical analgesia. Objectives: To evaluate the effect of a single intraoperative administration of liposome bupivacaine on postsurgical pain, opioid use and opioid-related side effects in subjects undergoing breast surgery and/or abdominoplasty. Methods: In the present phase IV, multicentre, prospective observational study, subjects received a single intraoperative administration (266 mg) of liposome bupivacaine. Rescue analgesia was available to all subjects as needed. Outcome measures, assessed through postoperative day 3, included postsurgical pain intensity (11-point numerical rating scale), opioid consumption and overall benefit of analgesic score. Results were evaluated comparing investigators' previous experience with similar surgeries. Results: Forty-nine subjects entered the study: 34 underwent breast surgery only and 15 underwent abdominoplasty with or without breast surgery (six underwent breast surgery in addition to abdominoplasty). Mean numerical rating scale pain scores remained ≤4.3 from discharge through postoperative day 3. Median daily oral opioid consumption was approximately 1.0 tablet postoperatively on the day of surgery and was approximately 2.0 tablets by postoperative day 3. Mean overall benefit of analgesic score ranged between 2.8 and 4.9 throughout the study. Conclusion: In this particular subject population, liposome bupivacaine was associated with low pain intensity scores and reduced opioid consumption compared with the investigators' previous experiences. Subjects' satisfaction with postsurgical analgesia was high, with a low burden of opioid-related side effects.